A review of dynamic motion control considering physics for real time animation character - Yusof, Suhaimi (2011)
This paper presents a current motion research in the real time animation character. Real time animation character has the problem with unrealistic and unnatural character movement. This review focuses on three main parts in dynamic motion generation with physics consideration and control: skeleton hierarchy and kinematics, motion capture data animation, and active dynamic control.